2019
DOI: 10.1177/1940082919864262
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer, Antibacterial, and Phytochemicals Derived From Extract of Aerva javanica (Burm.f.) Juss. ex Schult. Grown Naturally in Saudi Arabia

Abstract: Aerva javanica (Burm.f.) Juss. ex Schult. (Amaranthaceae family) has many pharmaceutical properties. This study aimed to determine the anticancerous effect of A. javanica methanol extract (AJME) on breast cancer cell lines and prostate cancer cell lines. The antibacterial potency of A. javanica solvent extracts was tested against Micrococcus luteus, Staphylococcus aureus, Pseudomonas aeruginosa, and Shigella flexneri. A screening of five concentrations of A. javanica was done on prostate and breast cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Our results show that the A. javanica flowers' EO is a rich source of potential hydrocarbons, and supporting the results published by Samejo et al [12] and Samejo et al [13]. Our results are justifying the rich ethnomedicinal applications of flowers [14,15]. Angustione is a ketone reported to have antioxidant, anticancer, and antiviral (anti-HIV) biological activity [16].…”
Section: Chemical Composition (By Gc-ms)supporting
confidence: 91%
“…Our results show that the A. javanica flowers' EO is a rich source of potential hydrocarbons, and supporting the results published by Samejo et al [12] and Samejo et al [13]. Our results are justifying the rich ethnomedicinal applications of flowers [14,15]. Angustione is a ketone reported to have antioxidant, anticancer, and antiviral (anti-HIV) biological activity [16].…”
Section: Chemical Composition (By Gc-ms)supporting
confidence: 91%
“…The potent activity was related to the active components of S. persica, including flavonoids, salvadorine, alkaloids, cyanogenic, salvadourea, glycosides, and tannins, which are known to possess strong antimicrobial activity [131][132][133]. Methanolic extracts from the leaves, stem, flower, and fruit of Conocarpus erectus L. and the leaves of Aerva javanica exhibited strong antibacterial activity against Bacillus subtilis, S. aureus, and the acid-fast bacterium Mycobacterium phlei [134][135][136]. Furthermore, the methanolic extracts of Mentha × piperita and Mentha longifolia populations grown in northern SA showed that M. × piperita contained the flavonoids naringin 328.8 mg/100 g DW, cynaroside 162.8 mg/100 g DW, and higher phenolic acid content than M. longifolia: rosmarinic acid 1547.6 mg/100 g DW, cryptochlorogenic acid 91.7 mg/100 g DW, and chlorogenic acid 69.4 mg/100 g DW.…”
Section: Antibacterial Activity Of Saudi Arabian Plants and Their Pot...mentioning
confidence: 99%
“…Each extract was tested against 4 bacteria species, and methanolic extract was most active. 187 Whole plant was extracted with acetone, ethanol, methanol and water, and essential oil was also prepared. All products were tested against several species of bacteria and fungi.…”
Section: Activity/property Major Findings/referencementioning
confidence: 99%